O trabalho das mulheres e a agroecologia nos assentamentos Antonio Companheiro Tavares em São Miguel do Iguaçu e a Ander Rodolfo Henrique em Diamante do Oeste - Paraná - Refati, Daiana Caroline (2015)
The research, the work of women in the Ander Rodolfo Henrique settlements in the municipality of Diamante do Oeste and the Antonio Companheiro Tavares settlement in the municipality of São Miguel do Iguaçu aimed to analyze how gender relations are established, identifying the activities that women do in their lots. Another focus of the research is the agro-ecological production, both settlements are building the transition to agroecology. Therefore, we tried to discuss on the peasants' struggle for land in Brazil and Paraná, from the distant past to the present day with the emergence of the MST. Through the social movements, peasant and farmers have acquired a number of achievements, among them the lands of the settlements. From the moment of the conquest of the land, we seek to understand how was the trajectory of the fight of the peasants since the camping period. Already settled, our goal was to identify the lifestyles that are created and recreated by the families, including agro-ecological production and especially gender relations. From the analysis of gender relations we identified mechanisms that give conditions for the establishment of equal relations, corporatism and the insertion of women in activities historically associated with the family patriarch. Despite this, there still is the reproduction of unequal power relations, of submission, sexism, either under the domestic, productive work - when women are excluded from certain decision making spaces, especially those involving income and commercialization - and militancy. The versions of the women provided subsidies in the analysis about their places, acting and roles in the settlements